Postgraduate students' understanding of mixed methods research design at the proposal stage - Mabila, T.E. (South African Journal of Higher Education, 2017)
Mixed methods research (MMR) design by postgraduate students planning their research projects is on the rise. However, little is known about their conception of this relatively new methodology as their research begins. We report on an exploratory inquiry into the understanding of MMR by postgraduate students in a South African comprehensive university as revealed in their research proposals. We employed document analysis to examine a total of 67 proposals, and found conflicting and divergent interpretations of MMR. Most proposals gave no philosophical foundation for choosing particular methodological combinations; many were unclear about the selected design, lacked pertinent methodological information, provided insufficient justification for choice of study design, and lacked rigour in addressing data collection and analysis. This situation may have detrimental consequences for the university’s growth of research capacity in this area and future research culture. We conclude with MMR recommendations for research committees, supervisors and candidates for research degrees.